PARADOX OF THE REWARD SYSTEM: CAN REWARDS STRENGTHEN OR WEAKEN THE INFLUENCE OF PERFORMANCE ON JOB SATISFACTION? - Fathorrahman, Fathorrahman; Anjaningrum, Widiya Dewi; Karnawati, Tin Agustina; Nurmayanti, Siti; Soares, Agusto da Conceicao (Veredas do Direito, 2026)
As one of the university's resources, lecturers play a strategic role in the academic and educational development of students. The government must establish regulations regarding the profession, career, and income of lecturers because the widespread phenomenon of low lecturer salaries indicates that there are factors that are still not commensurate with their level of education. When a lecturer has positive feelings about their work, it's called job satisfaction. So, job satisfaction, performance, and the faculty reward system are very important for universities. This research was conducted using a quantitative method. Purposive sampling is the sampling technique used in this study. This research involved 260 faculty samples from excellent accredited private universities in the cities of Malang, Surabaya, and Jember in East Java, as well as Mataram in West Nusa Tenggara. A total of 245 questionnaires were collected out of 260 distributed and processed using Structural Equation Modelling - Partial Least Squares (SEM-PLS) analysis. The research results indicate that the reward system does not have a direct impact on job satisfaction, but it does have a direct impact on performance and is proven to moderate the influence of performance on job satisfaction. Performance significantly influences job satisfaction and is proven to fully mediate the impact of reward systems on job satisfaction.